Desenvolvimento de uma plataforma computacional gráfica e de código aberto para estudos de sistemas de potência - Oliveira, Thales Lima (2016)
The computational analysis of power systems has become each day wider and more complex. It was developed several commercial and free simulators capable of performing various calculations using mathematical models of the electrical network components. The commercial software, usually not free, prevents the insertion and customization of new tools for having the source code closed, protected by proprietary licenses. As opposed to these private programs, it was born the concept of open-source, which promotes free access to information, including the source code, free of charge. Some open-source applications have been developed in the field of electric power systems, but there are some deficiencies in these programs, such as the lack of a friendly Graphical User Interface (GUI), proprietary software dependency and discontinuation in the development. Within this context, it was begun the development of the PSP-UFU (Power System Platform of the Federal University of Uberlândia), aimed to load flow calculation, short circuit calculations and dynamic analysis of any power system. This platform is open-source and have a friendly GUI, allowing the construction of any power grid through the manipulation of visual elements. It was used the C++, a free popular programming language with widespread application in academia, in addition to being object-oriented, which was the paradigm used in the conception of this program. To create the GUI it was used the wxWidgets framework, which allows the development of multiplatform programs. Were built the 14 and 118-bus IEEE test systems to validate the developed calculation tools. The results from PSP-UFU were compared to those originated from ANAREDE and ANAFAS, which are programs already well-established in the brazilian electricity sector.